Implementing Community-based Participatory Research in the study of substance use and service utilisation in Eastern European and Turkish communities in Belgium. (4th May 2017) - De Kock, Charlotte; Schamp, Julie; Vanderplasschen, Wouter; Decorte, Tom; Derluyn, Ilse; Hauspie, Bert; Jacobs, Dirk; Sacco, Muriel
Abstract: Community-Based Participatory Research (CBPR) is an effective strategy to promote action research regarding health and substance use issues. The London-based Centre for Ethnicity and Health's CBPR model was replicated in Belgium to study substance use and service utilisation in Bulgarian, Slovakian and Turkish communities in the city of Ghent. This article focuses on the implementation of the CBPR model, challenges and adaptions linked to the Belgian context. In this paper, we describe the study design and actors involved, namely (1) community organisations, (2) the community advisory board and (3) community researchers. Furthermore, we focus on the challenges and pitfalls of the CBPR method and its implications, including (1) community collaboration, (2) co-ethnic researchers, (3) characteristics of the respondents and (4) empowerment of the respective communities. We conclude by discussing potential pathways for future CBPR in the field of substance use and service utilisation among migrants and ethnic minorities.